2021
DOI: 10.3390/nu13041296
|View full text |Cite
|
Sign up to set email alerts
|

Hypomagnesemia Is a Risk Factor for Infections after Kidney Transplantation: A Retrospective Cohort Analysis

Abstract: Introduction: Magnesium (Mg2+) deficiency is a common finding in the early phase after kidney transplantation (KT) and has been linked to immune dysfunction and infections. Data on the association of hypomagnesemia and the rate of infections in kidney transplant recipients (KTRs) are sparse. Methods: We conducted a single-center retrospective cohort study of KTRs transplanted between 2005 and 2015. Laboratory data, including serum Mg2+ (median time of the Mg2+ measurement from KT: 29 days), rate of infections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 63 publications
0
5
1
Order By: Relevance
“…28 Previous clinical studies also demonstrated that hypomagnesemia was associated with an increased risk of infection in kidney transplantation patients. 7,8 In the present study, kidney function and gastrointestinal symptoms in the infection group were not significantly different from those in the noninfection group. The baseline serum magnesium level in the infection group of new-onset SLE patients was lower than that in the noninfection group.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…28 Previous clinical studies also demonstrated that hypomagnesemia was associated with an increased risk of infection in kidney transplantation patients. 7,8 In the present study, kidney function and gastrointestinal symptoms in the infection group were not significantly different from those in the noninfection group. The baseline serum magnesium level in the infection group of new-onset SLE patients was lower than that in the noninfection group.…”
Section: Discussioncontrasting
confidence: 62%
“…5,6 In kidney transplantation patients, a lower baseline serum magnesium concentration is associated with an increased risk of infection. 7,8 Recently, a cross-sectional study indicated that higher dietary magnesium intake was associated with lower coronavirus disease 2019 (COVID-19) severity and related symptoms in hospitalized patients. 9 Another nationwide retrospective cohort study in the United States demonstrated that populations in low-magnesium areas were associated with a higher risk of early transmission in COVID-19 infection.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging data indicate a potential relationship between Mg and immune system functions. Mg is integral to various immune processes, including immunoglobulin creation, immune cell attachment, and antibody-driven cytolysis [ 23 ]. The current study demonstrated an association between hypomagnesemia and admission due to infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium deficit exhibits diabetogenic effects and it represents a proven independent risk factor for post-transplant diabetes mellitus [ 48 , 49 ]. Recent data also note the increased risk of Mg depleted patients to develop urinary tract infections and viral infections [ 50 ].…”
Section: Hypomagnesemiamentioning
confidence: 99%